Implementation and Comparison of Controllers for Planar Robots - Urrea-Onate, E; Kern-Molina, J (Korean Institute of Electrical Engineers, 2017)
The nonlinear behavior and the high performance requirement are the main problems that appear in the design of manipulator robots and their controllers. For that reason, the simulation, real-time execution and comparison of the performance of controllers applied to a robot with three degrees of freedom are presented. Five controllers are prepared to test the robot s dynamic model: predictive; hyperbolic sine-cosine; sliding mode; hybrid composed of a predictive + hyperbolic sine-cosine controller; and adaptive controller. A redundant robot, a communication and signal conditioning interface, and a simulator are developed by means of the MatLab/Simulink software, which allows analyzing the dynamic performance of the robot and of the designed controllers. The manipulator robot is made to follow a test trajectory which, thanks to the proposed controllers, it can do. The results of the performance of this manipulator and of its controllers, for each of the three joints, are compared by means of RMS indices, considering joint errors according to the imposed trajectory and to the controller used. © The Korean Institute of Electrical Engineers.